2021
DOI: 10.3390/ani11010192
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis of Growth Curve Parameters in Chinese Simmental Beef Cattle

Abstract: The objective of the present study was to perform a genome-wide association study (GWAS) for growth curve parameters using nonlinear models that fit original weight–age records. In this study, data from 808 Chinese Simmental beef cattle that were weighed at 0, 6, 12, and 18 months of age were used to fit the growth curve. The Gompertz model showed the highest coefficient of determination (R2 = 0.954). The parameters’ mature body weight (A), time-scale parameter (b), and maturity rate (K) were treated as phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 50 publications
(31 reference statements)
2
33
0
Order By: Relevance
“…Body weight was measured for each individual at 0, 6, 12, and 18 months after birth, respectively. Here, the body weight data were consistent with the data in the study by Duan et al [ 24 ].…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…Body weight was measured for each individual at 0, 6, 12, and 18 months after birth, respectively. Here, the body weight data were consistent with the data in the study by Duan et al [ 24 ].…”
Section: Methodssupporting
confidence: 91%
“…Notably, intramuscular fat becomes an important component of maturing muscles, and the mass of skeletal muscle accounts for 40% of total body weight in animals [ 32 ], thus it could be speculated that ANGPTL4 might regulate BW trait by influencing the formation of adipose tissue. Additionally, previous studies have reported ANGPTL2 , a homologous family gene of ANGPTL4 , influences the development of the bovine BW trait [ 24 ]. Taken together, ANGPTL4 could be recognized as the candidate gene regulating the BW trait for further research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations